A Comprehensive Systematic Review of Relationship between Surgery Waiting Time and Perforation Rate in Acute Appendicitis - Putra Intan Sanjaya; Nikma Nur Fadhila (The International Journal of Medical Science and Health Research, 2026)
Introduction: Acute appendicitis is one of the most common surgical emergencies worldwide, with appendiceal perforation representing a critical complication associated with significant morbidity. The relationship between surgical waiting time and perforation risk remains controversial, with conflicting evidence regarding the safety of in-hospital delay. This systematic review aims to evaluate the association between waiting time for appendectomy and perforation rates in acute appendicitis, identify population-specific risks, and synthesize evidence for clinical practice guidance. Methods: A systematic review was conducted using comprehensive literature screening. Studies were included if they examined patients with acute appendicitis, reported measurable waiting time intervals, documented perforation outcomes, and employed appropriate comparative study designs. Data extraction encompassed waiting time definitions, perforation criteria, study population characteristics, statistical relationships, perforation rates by time categories, confounding factors, and secondary outcomes. Harvard citation style was applied throughout. Results: Eighty-nine studies published were analyzed, comprising retrospective cohorts (n=67), prospective cohorts (n=12), randomized controlled trials (n=2), cross-sectional studies (n=7), and one systematic review. Sample sizes ranged from 50 to 683,590 patients. Overall perforation rates varied from 7.5% to 72.5%, with most studies reporting 10-30%. For pre-hospital delay (symptom duration), consistent positive association with perforation was demonstrated, with odds ratios increasing from 2.84 for >24-hour delay to 6.6 for >36-hour symptoms (Bickell et al., 2006; Sadot et al., 2013). However, for in-hospital delay, findings were discordant. The PERFECT randomized controlled trial found no significant difference in perforation rates between <8-hour (8%) and <24-hour (9%) surgical windows (absolute risk difference 0.6%, 95% CI -2.1 to 3.2; Jalava et al., 2023). Conversely, pediatric studies demonstrated significant associations, with every hour of delay increasing perforation odds by 2% (AOR 1.02, 95% CI 1.00-1.04; Meltzer et al., 2016). High-risk subgroups including elderly patients, those with appendicoliths, and patients with marked inflammatory markers demonstrated accelerated perforation risk with in-hospital delay (Jeon et al., 2018; Hanson et al., 2019). Discussion: The relationship between surgical waiting time and appendiceal perforation is fundamentally dichotomous. Pre-hospital delay consistently predicts perforation at presentation, representing irreversible disease progression. In contrast, in-hospital delay of up to 24 hours appears safe for carefully selected adults with uncomplicated appendicitis, likely attributable to preoperative antibiotics and modern diagnostic accuracy. However, this safety window does not extend uniformly across populations. Pediatric patients demonstrate time-dependent perforation risk even within 24 hours, potentially reflecting anatomical and physiological differences in disease progression (Serres et al., 2017; Stevenson et al., 2017). Elderly patients present with attenuated symptoms yet accelerated perforation, warranting expedited surgical intervention (F. Rondelli et al., 2019). The presence of appendicolith confers 2.2-fold increased risk of progression to complicated appendicitis within 12 hours, mandating prioritized surgical scheduling (M. Prayle et al., 2023). Secondary outcomes including length of stay and surgical site infections showed inconsistent associations with in-hospital delay, further supporting risk-stratified rather than universal timing protocols. Conclusion: This systematic review demonstrates that the impact of surgical waiting time on appendiceal perforation is critically dependent on the temporal phase examined and patient-specific risk factors. Pre-hospital delay is a robust predictor of perforation, whereas in-hospital delay up to 24 hours is acceptable for low-risk adults with uncomplicated appendicitis. However, pediatric patients, elderly individuals, and those with appendicoliths or severe inflammatory markers require expedited surgery within 12 hours of presentation. We recommend implementation of risk-stratified triage protocols incorporating clinical, laboratory, and radiological parameters to optimize surgical timing. Future research should focus on prospective validation of composite risk stratification models and investigation of antibiotic therapy optimization during waiting periods. Healthcare institutions should prioritize public education to reduce pre-hospital delay while allocating resources for timely surgical intervention in high-risk populations.